(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The article reviews the journey discourses in two narratives written by two women during the imperialist period of the fin de siècle, who traveled through marginal spaces to modernity. The first author is Florence Dixie, an English noblewoman who writes her travelogue to Patagonia during 1879, while Iris (Inés Echeverría Bello), an equally aristocratic, and Chilean woman, writes her journey made through Ranco lake in 1910. Independent of nationality of origin of these women and their personal differences, as long as the role played by them in the expedition group, both traveling writers are repositories of an imperial gace, that shows in the way they go into theirs narrative through the spaces explored.